Remaking multilingualism : a translanguaging approach - Otcu-Grillman, Bahar; Borjian, Maryam; García, Ofelia (Translanguaging in theory and practice, 2022)
"This book is both a collection of cutting-edge research in the areas of multilingualism, translanguaging and bilingual education, and a tribute to the research and influence of Ofelia García. It recognizes Ofelia García's contribution as both a scholar and friend, and her place at the centre of a movement dedicated to equality and inclusion"--